Keberadaan Layanan Remaja Untuk Meningkatkan Minat Baca Remaja di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Fitri, Restia Ainil; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the existence of Youth Services to Improve Adolescent Reading Interest at the Library and Archives of West Sumatra province. This article aims to describe: (1) the existence of juvenile services for improving adolescent reading, (2) problems were found in the increase reading adolescents in juvenile services, and (3) efforts to be made to overcome the obstacles in improving adolescent reading in adolescent services. Data collected through observation, interviews, and literature. Analyzing data descriptively. By analyzing the data, it was concluded the following. First, the presence of juvenile services has not been put to good use by library users, especially for teenagers library users junior high, high school, and Students; Second, problems were found to increase reading in adolescents; Third, efforts should be made to overcome the obstacles in improving adolescent reading. Keywords: juvenile services; interest in reading; libraries and archives